1996
DOI: 10.1083/jcb.134.3.647
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-modified, cysteinyl-containing peptides of diverse structures are efficiently S-acylated at the plasma membrane of mammalian cells.

Abstract: Abstract. A variety of cysteine-containing, lipidmodified peptides are found to be S-acylated by cultured mammalian cells. The acylation reaction is highly specific for cysteinyl over serinyl residues and for lipid-modified peptides over hydrophilic peptides. The S-acylation process appears by various criteria to be enzymatic and resembles the S-acylation of plasma membrane-associated proteins in various characteristics, including inhibition by tunicamycin. The substrate range of the S-acylation reaction encom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(87 citation statements)
references
References 93 publications
(145 reference statements)
7
79
1
Order By: Relevance
“…The results of the biophysical and cell biology investigations support a model [51] for specific localization of proteins by myristoylation/ palmitoylation or farnesylation/palmitoylation. According to this model, the specific localization is not only determined by the lipid groups introduced in the course of the biosynthesis (in the case of Ras proteins, the farnesyl residue).…”
Section: Scheme 4 Scheme 5 Synlettsupporting
confidence: 53%
See 2 more Smart Citations
“…The results of the biophysical and cell biology investigations support a model [51] for specific localization of proteins by myristoylation/ palmitoylation or farnesylation/palmitoylation. According to this model, the specific localization is not only determined by the lipid groups introduced in the course of the biosynthesis (in the case of Ras proteins, the farnesyl residue).…”
Section: Scheme 4 Scheme 5 Synlettsupporting
confidence: 53%
“…This hypothesis was tested by in vivo studies with fluorescently labeled N-myristoylated [51] and S-farnesylated peptides. [43,50,51] Peptides 30 and 31 (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S-Acylation of H-and N-Ras occurs in an early compartment of the exocytotic pathway (Choy et al, 1999;Magee and Marshall, 1999;Apolloni et al, 2000). Studies with lipid-modified peptides have shown that efficient S-acylation can occur directly at the PM (Schroeder et al, 1996) and that doubly lipidated peptides are bound to membrane vesicles by kinetic trapping (Shahinian and Silvius, 1995). Whether K-Ras exists in a dynamic equilibrium and can rapidly switch between a PM-bound and a cytosolic form (Yokoe and Meyer, 1996) or shows fast lateral diffusion at the PM (Niv et al, 1999) is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have demonstrated that short peptide sequences are sufficient to direct the addition of both lipids and confer plasma membrane targeting (Schroeder et al, 1996(Schroeder et al, , 1997Wolven et al, 1997) (this study). Biophysical measurements of the association of lipid-modified peptides with artificial bilayers provide a rationale for the requirement of two lipid modifications in targeting proteins to membranes (Peitzsch and McLaughlin, are targeted to the plasma membrane via their association with Gpa1p, which is dually acylated.…”
Section: Plasma Membrane-targeting Via Lipid Modifications and Proteimentioning
confidence: 99%